Relationships between coping strategies and mood states in caregivers of people with dementia in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University - Dominy, Jean Beatrice (Massey University, 2004)
Alzheimer's dementia is a worldwide concern, as is the growing aging population and demands on services by many elderly people. Caregiving for people with dementia is recognised as one of the most distressing events in any family's life cycle. Many adverse effects among caregivers have been identified, such as increased depression and anxiety, however many questions remain unanswered. New Zealand, in particular, lacks accurate information on caregivers of people with dementia, obviously affecting the programmatic and clinical decisions made about this group. This study investigates the role of helping attitudes and coping strategies on the mood states (positive and negative affect) of caregivers of people with dementia. A regional sample, recruited through the membership lists of Age Concern and the Alzheimer's Society, consisted of 158 caregivers. A self-report questionnaire was developed for the study using three instruments: Helping Attitude Scale (HAS), Revised Ways of Coping Checklist (RWCCL), Positive and Negative Affect Scales (PANAS). A range of demographic information was also included in the questionnaire. The results provide a description of the characteristics of New Zealand caregivers and found that helping attitudes and coping strategies each contribute in different ways to positive and negative mood states, and differentially predict affective outcomes in caregivers of people with dementia. The results may assist practitioners to identify caregivers who may be at risk for developing mood difficulties and allow for the implementation of appropriate psychological intervention and prevention strategies.
Keywords: Caregivers -- Psychology; Alzheimer's disease -- Patients -- Family relations